Role of Bile Acid Receptors in the Development and Function of Diabetic Nephropathy - Yuanyuan Fang; Minjing Qin; Qitong Zheng; Kuilong Wang; Xin Han; Qiao Yang; Xia'nan Sang; Gang Cao (Kidney International Reports)
Diabetic nephropathy (DN) is a prevalent microvascular complication that occurs often in individuals with diabetes. It significantly raises the mortality rate of affected patients. Therefore, there is an urgent need to identify therapeutic targets for controlling and preventing the occurrence and development of DN. Bile acids (BAs) are now recognized as intricate metabolic integrators and signaling molecules. The activation of BAs has great promise as a therapeutic approach for preventing DN, renal damage caused by obesity, and nephrosclerosis. The nuclear receptors (NRs), farnesoid X receptor (FXR), pregnane X receptor (PXR), vitamin D receptor (VDR); and the G protein-coupled BA receptor, Takeda G-protein-coupled receptor 5 (TGR5) have important functions in controlling lipid, glucose, and energy metabolism, inflammation, as well as drug metabolism and detoxification. Over the past 10 years, there has been advancement in comprehending the biology and processes of BA receptors in the kidney, as well as in the creation of targeted BA receptor agonists. In this review, we discuss the role of BA receptors, FXR, PXR, VDR, and TGR5 in DN and their role in renal physiology, as well as the development and application of agonists that activate BA receptors for the treatment of kidney diseases.